let n be Nat; :: thesis: for h, x being Real
for f1, f2 being Function of REAL,REAL holds ((cdif ((f1 - f2),h)) . (n + 1)) . x = (((cdif (f1,h)) . (n + 1)) . x) - (((cdif (f2,h)) . (n + 1)) . x)

let h, x be Real; :: thesis: for f1, f2 being Function of REAL,REAL holds ((cdif ((f1 - f2),h)) . (n + 1)) . x = (((cdif (f1,h)) . (n + 1)) . x) - (((cdif (f2,h)) . (n + 1)) . x)
let f1, f2 be Function of REAL,REAL; :: thesis: ((cdif ((f1 - f2),h)) . (n + 1)) . x = (((cdif (f1,h)) . (n + 1)) . x) - (((cdif (f2,h)) . (n + 1)) . x)
defpred S1[ Nat] means for x being Real holds ((cdif ((f1 - f2),h)) . (\$1 + 1)) . x = (((cdif (f1,h)) . (\$1 + 1)) . x) - (((cdif (f2,h)) . (\$1 + 1)) . x);
A1: S1[ 0 ]
proof
let x be Real; :: thesis: ((cdif ((f1 - f2),h)) . (0 + 1)) . x = (((cdif (f1,h)) . (0 + 1)) . x) - (((cdif (f2,h)) . (0 + 1)) . x)
x - (h / 2) in REAL by XREAL_0:def 1;
then ( x - (h / 2) in dom f1 & x - (h / 2) in dom f2 ) by FUNCT_2:def 1;
then x - (h / 2) in (dom f1) /\ (dom f2) by XBOOLE_0:def 4;
then A2: x - (h / 2) in dom (f1 - f2) by VALUED_1:12;
x + (h / 2) in REAL by XREAL_0:def 1;
then ( x + (h / 2) in dom f1 & x + (h / 2) in dom f2 ) by FUNCT_2:def 1;
then x + (h / 2) in (dom f1) /\ (dom f2) by XBOOLE_0:def 4;
then A3: x + (h / 2) in dom (f1 - f2) by VALUED_1:12;
((cdif ((f1 - f2),h)) . (0 + 1)) . x = (cD (((cdif ((f1 - f2),h)) . 0),h)) . x by Def8
.= (cD ((f1 - f2),h)) . x by Def8
.= ((f1 - f2) . (x + (h / 2))) - ((f1 - f2) . (x - (h / 2))) by Th5
.= ((f1 . (x + (h / 2))) - (f2 . (x + (h / 2)))) - ((f1 - f2) . (x - (h / 2))) by
.= ((f1 . (x + (h / 2))) - (f2 . (x + (h / 2)))) - ((f1 . (x - (h / 2))) - (f2 . (x - (h / 2)))) by
.= ((f1 . (x + (h / 2))) - (f1 . (x - (h / 2)))) - ((f2 . (x + (h / 2))) - (f2 . (x - (h / 2))))
.= ((cD (f1,h)) . x) - ((f2 . (x + (h / 2))) - (f2 . (x - (h / 2)))) by Th5
.= ((cD (f1,h)) . x) - ((cD (f2,h)) . x) by Th5
.= ((cD (((cdif (f1,h)) . 0),h)) . x) - ((cD (f2,h)) . x) by Def8
.= ((cD (((cdif (f1,h)) . 0),h)) . x) - ((cD (((cdif (f2,h)) . 0),h)) . x) by Def8
.= (((cdif (f1,h)) . (0 + 1)) . x) - ((cD (((cdif (f2,h)) . 0),h)) . x) by Def8
.= (((cdif (f1,h)) . (0 + 1)) . x) - (((cdif (f2,h)) . (0 + 1)) . x) by Def8 ;
hence ((cdif ((f1 - f2),h)) . (0 + 1)) . x = (((cdif (f1,h)) . (0 + 1)) . x) - (((cdif (f2,h)) . (0 + 1)) . x) ; :: thesis: verum
end;
A4: for k being Nat st S1[k] holds
S1[k + 1]
proof
let k be Nat; :: thesis: ( S1[k] implies S1[k + 1] )
assume A5: for x being Real holds ((cdif ((f1 - f2),h)) . (k + 1)) . x = (((cdif (f1,h)) . (k + 1)) . x) - (((cdif (f2,h)) . (k + 1)) . x) ; :: thesis: S1[k + 1]
let x be Real; :: thesis: ((cdif ((f1 - f2),h)) . ((k + 1) + 1)) . x = (((cdif (f1,h)) . ((k + 1) + 1)) . x) - (((cdif (f2,h)) . ((k + 1) + 1)) . x)
A6: ( ((cdif ((f1 - f2),h)) . (k + 1)) . (x - (h / 2)) = (((cdif (f1,h)) . (k + 1)) . (x - (h / 2))) - (((cdif (f2,h)) . (k + 1)) . (x - (h / 2))) & ((cdif ((f1 - f2),h)) . (k + 1)) . (x + (h / 2)) = (((cdif (f1,h)) . (k + 1)) . (x + (h / 2))) - (((cdif (f2,h)) . (k + 1)) . (x + (h / 2))) ) by A5;
A7: (cdif ((f1 - f2),h)) . (k + 1) is Function of REAL,REAL by Th19;
A8: (cdif (f2,h)) . (k + 1) is Function of REAL,REAL by Th19;
A9: (cdif (f1,h)) . (k + 1) is Function of REAL,REAL by Th19;
((cdif ((f1 - f2),h)) . ((k + 1) + 1)) . x = (cD (((cdif ((f1 - f2),h)) . (k + 1)),h)) . x by Def8
.= (((cdif ((f1 - f2),h)) . (k + 1)) . (x + (h / 2))) - (((cdif ((f1 - f2),h)) . (k + 1)) . (x - (h / 2))) by
.= ((((cdif (f1,h)) . (k + 1)) . (x + (h / 2))) - (((cdif (f1,h)) . (k + 1)) . (x - (h / 2)))) - ((((cdif (f2,h)) . (k + 1)) . (x + (h / 2))) - (((cdif (f2,h)) . (k + 1)) . (x - (h / 2)))) by A6
.= ((cD (((cdif (f1,h)) . (k + 1)),h)) . x) - ((((cdif (f2,h)) . (k + 1)) . (x + (h / 2))) - (((cdif (f2,h)) . (k + 1)) . (x - (h / 2)))) by
.= ((cD (((cdif (f1,h)) . (k + 1)),h)) . x) - ((cD (((cdif (f2,h)) . (k + 1)),h)) . x) by
.= (((cdif (f1,h)) . ((k + 1) + 1)) . x) - ((cD (((cdif (f2,h)) . (k + 1)),h)) . x) by Def8
.= (((cdif (f1,h)) . ((k + 1) + 1)) . x) - (((cdif (f2,h)) . ((k + 1) + 1)) . x) by Def8 ;
hence ((cdif ((f1 - f2),h)) . ((k + 1) + 1)) . x = (((cdif (f1,h)) . ((k + 1) + 1)) . x) - (((cdif (f2,h)) . ((k + 1) + 1)) . x) ; :: thesis: verum
end;
for n being Nat holds S1[n] from NAT_1:sch 2(A1, A4);
hence ((cdif ((f1 - f2),h)) . (n + 1)) . x = (((cdif (f1,h)) . (n + 1)) . x) - (((cdif (f2,h)) . (n + 1)) . x) ; :: thesis: verum